Healing at the margins: discourses of culture and illness in psychiatrists', psychologists' and indigenous healers' talk about collaboration - Yen, Jeffery (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
This dissertation explores discourses about culture and illness in the talk of mental health professionals and indigenous healers. It represents an attempt to situate the issue of indigenous healing in South Africa within a particular strand of critical discourse analytic research. In the context of current deliberations on the value, or otherwise, of indigenous healing in a changing health and specifically mental health system, the talk of both mental health practitioners and indigenous healers as they conceptualise "disorder" , and discuss possibilities for collaboration, is chosen as a specific focus for this study. Disputes over what constitutes "disorder" both within mental health, and between mental health and indigenous healing are an important site in which the negotiation of power relations between mental health professionals and indigenous healers is played out. The results of this study suggest that despite the construction of cogent commendations for the inclusion of indigenous healing in mental health, it remains largely marginalised within talk about mental health practice. While this study reproduces to some extent the marginalisation of indigenous healing discourse, it also examines some of the discursive practices and methodological difficulties implicated in its marginalisation. However, in the context of "cultural pride strategies" associated with talk about an African Renaissance, indigenous healing may also function as a site of assertion of African power and resistance in its construction as an essentially African enterprise. At the same time, it may achieve disciplinary effects consonant with cultural pride strategies, in constructing afflictions in terms of neglect of, or disloyalty to cultural tradition. These results are discussed in terms of the methodological difficulties associated with interviewing and discourse analysis of translated texts, which contributes to difficulties with articulating indigenous healing discourse in a way that challenges the dominant psychiatric discourses implicated in its marginalisation within mental health. It concludes with recommendations for future research which addresses indigenous healing discourse in its own terms, and examines its operation as a disciplinary apparatus in South African society.
Keywords: Traditional medicine -- South Africa; Medical policy -- South Africa; Mental health -- South Africa; Healers -- South Africa